2017
DOI: 10.1080/19336896.2017.1314427
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid- and FDG-PET in sporadic Creutzfeldt-Jakob disease: Correlation with pathological prion protein in neuropathology

Abstract: Our study supports the use of FDG-PET in the assessment of CJD. FDG-PET may be especially useful in cases of suspected CJD and negative MRI. Furthermore, this case report provides more evidence about the behavioral of amyloid tracers, and the possibility of a low-affinity binding to other non-amyloid proteins, such as the pathological prion protein, is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Broadly, 18 F-FDG-PET was suggested to be of diagnostic relevance in the differential diagnosis of sCJD from other forms of rapidly progressive dementia in a few cases and series. The parietooccipital cortex was mainly affected with hypometabolism in patients with visual symptoms which is in line with our findings [19,20]. However, the diagnostic relevance of 18 F-FDG-PET imaging in differential diagnosis of Heidenhain-variant sCJD remains elusive due to a lack of prospective trials but can be considered in unclear cases of rapidly progressive dementia.…”
Section: Discussionsupporting
confidence: 88%
“…Broadly, 18 F-FDG-PET was suggested to be of diagnostic relevance in the differential diagnosis of sCJD from other forms of rapidly progressive dementia in a few cases and series. The parietooccipital cortex was mainly affected with hypometabolism in patients with visual symptoms which is in line with our findings [19,20]. However, the diagnostic relevance of 18 F-FDG-PET imaging in differential diagnosis of Heidenhain-variant sCJD remains elusive due to a lack of prospective trials but can be considered in unclear cases of rapidly progressive dementia.…”
Section: Discussionsupporting
confidence: 88%
“…Considering to brain metabolism, however, a recent study indicated the [ 18 F]-AV-1451 PET was not suitable for patients with RPD due to sCJD, due to different pathological process [8]. As for the technique of FDG-PET, it has an established role in the diagnostic workup of patients with sCJD [9,10]. We have summarized a table showing the changes in FDG-PET in sCJD patients reported from literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the imaging of prion diseases was well reviewed by Macfarlane et al , in 2007. [ 2 ] There are also more recent reports of imaging with other PET tracers such as translocator protein (TSPO) ligands, dueterodeprenyl PET for microglial activation, florbetaben for amyloid deposition and oxygen-15 water for blood flow,[ 20 21 22 23 ] and a report correlating FDG PET with cerebral blood flow measured by MR arterial spin labeling. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the imaging of prion diseases was well reviewed by Macfarlane et al, in 2007. [2] There are also more recent reports of imaging with other PET tracers such as translocator protein (TSPO) ligands, dueterodeprenyl PET for microglial activation, florbetaben for amyloid deposition and oxygen-15 water for blood flow, [20][21][22][23] and a report correlating FDG PET with cerebral blood flow measured by MR arterial spin labeling. [24] As in this case, multimodal neuroimaging can form an important part of the investigation of suspected prion disease, by detecting the combination of cortical diffusion-restriction and hypometabolism.…”
Section: Discussionmentioning
confidence: 99%